Dissection as a teaching tool: past, present, and future - Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos; García Rodríguez, María de Lourdes (2005)
Cultural changes, scientific progress, and new trends in medical education have modified the role of dissection in teaching anatomy in today's medical schools. We discuss in this article the role of dissection itself, the value of which has been under debate for the last 30 years. The importance of dissection is considered from different points of view: educational, bioethical, and human values. Included are different opinions from professors and students. Finally, the current practice of dissection is described for some universities in the United States and Europe, showing its use as a learning tool.